Migration and Imitation. (3rd November 2022) - Ivus, Olena; Naghavi, Alireza; Qiu, Larry D.
Abstract : This paper develops a North–South trade model with heterogeneous labour and horizontally differentiated products, and compares the implications of two policies: Southern intellectual property rights (IPR) and Northern immigration policy, with the latter aiming to attract Southern talent as a means of pre‐empting imitation. Individuals self‐select into becoming entrepreneurs and innovate (imitate) in the North (South). The likelihood of imitation depends on product quality, imitator's talent and IPR strength. Several interrelated channels of competition are identified. Allowing high‐talent migration when IPR protection in the South is weak shifts imitation to low‐quality products and innovation to high‐quality products. The outcome is in stark contrast to the policy of strengthening Southern IPR, which limits low‐talent imitation in the South and encourages low‐quality innovation in the North. Migration also increases the income of low‐talent entrepreneurs, as well as the average quality of products imitated by high‐talent entrepreneurs in the South. Global income rises with migration, but is not guaranteed to rise with stronger Southern IPR.